Summation of p-Faber series by the Abel–poisson method in the integral metric - Savchuk, V. V.; Savchuk, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We establish conditions on the boundary \( Γ \) of a bounded simply connected domain \( Ω \subset \mathbb{C} \) under which the p-Faber series of an arbitrary function from the Smirnov space \( {E_p}\left( Ω \right),1 \leqslant p < ∞ \), can be summed by the Abel–Poisson method on the boundary of the domain up to the limit values of the function itself in the metric of the space \( {L_p}\left( Γ \right) \).